Retinal artery occlusion and its association with stroke – literature review - Roskal-Wałek, Joanna; Mackiewicz, Jerzy; Wałek, Paweł; Gregorczyk, Marcin; Biskup, Michał; Wożakowska-Kapłon, Beata; Odrobina, Dominik (Medical Studies/Studia Medyczne, 2023)
Retinal artery occlusion (RAO) leads to acute retinal ischemia. Despite the low incidence rate of RAO, the occurrence of this condition has very important clinical implications. It is an emergency condition that requires urgent diagnostic evaluation and treatment. RAO is the ocular equivalent of acute cerebral ischemia. Patients with RAO have similar etiology and risk factors to patients with ischemic stroke and also are at high risk of subsequent cardiovascular events. However, the impact of RAO on the risk of a further ischemic stroke is still a matter of debate. Herein, we present a literature review on the relationship between RAO and stroke.